Counseling Communication in Improving Media Literacy of Subang Coastal Communities - Encep Dulwahab; Aep Kusnawan (Fakultas Dakwah dan Komunikasi UIN Sunan Gunung Djati Bandung, 2022)
Media literacy is a necessity for people who live in the midst of the development of communication technology. The overflow of information, and easy access to media, require the provision and strength to filter and criticize any content received by the public. By using descriptive methods, this study aims to determine how counselling communication can improve media literacy in the people of Desa Bojong Tengah, Kecamatan Pusakajaya, and Kabupaten Subang. The results showed that village government officials institutionally guide community leaders, community leaders informally and personally guide farmer groups, teachers guide formally guide students at school, and parents guide their children in a persuasive and coercive manner. The results of this study are expected to have an impact on the government in making regulations in increasing the importance of media literacy in the community and school environment. Then it has an impact on the formation of a special team that conducts media literacy counselling in each region.